TREE-RING EVIDENCE OF ‘LITTLE ICE AGE' GLACIER ADVANCES IN SOUTHERN TIBET - Brauning A. (My University, 2006)
The history of late Holocene glacier fluctuations in eastern Tibet was studied by determining the ages of trees growing on glacier deposits. Maximum tree ages yield minimum ages of AD 1760 and 1780 for moraine formation at the maximum extent of the ‘Little Ice Age' glacier advances in two glacier forefields. Subsequent moraines could be dated to the beginning of the nineteenth and the beginning of the twentieth century. Larch trees from a third glacier forefield in southeastern Tibet show evidence of glacier activity from 1580 to 1590, from the end of the eighteenth to the beginning of the nineteenth century and from 1860 to 1880. One glacier at Mt Gyalaperi recently advanced in both 1951 and 1987. Periods of glacier advances can partly be correlated with periods of growth reductions in chronologies of total ring width and maximum latewood density derived from trees growing on slopes above the glacier valleys. Correlation functions with meteorological data suggest that maximum latewood density of subalpine Picea balfouriana, Larix griffithii and Abies delavayi var. motouensis is positively correlated with summer temperature, while ring width of these species and of subalpine Juniperus tibetica is also sensitive to winter conditions prior to the growing season.
Keywords: DENDROGLACIOLOGY; DENDROCLIMATOLOGY; GLACIER HISTORY; SUMMER TEMPERATURES; 'LITTLE ICE AGE'; TIBETAN PLATEAU; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен